Practical Recommendations for High-Intensity Interval Training for Adults with Cardiovascular Disease. (September 2021) - Way, Kimberley L.; Terada, Tasuku; O'Neill, Carley D.; Vidal-Almela, Sol; Keech, Andrew; Reed, Jennifer L.
Apply It!: High-intensity interval training (HIIT) can be implemented safely in adults with cardiovascular disease (CVD) after a graded exercise test assessing exercise responses at a high intensity ( e.g., to 85% heart rate peak [HRpeak ] or a rating of perceived exertion [RPE] of 15). Always involve the patient in the decision-making process for selecting the mode of exercise to perform HIIT to increase adherence, compliance, and enjoyment to the exercise program. Given the low exercise tolerance that is typically experienced by patients with CVD, short duration high-intensity bouts ( e.g., 30 seconds to 1 minute) may be necessary to increase exercise tolerance and self-efficacy. Active or passive recovery interspersed between high-intensity intervals should be equal to or greater than the duration of the high-intensity intervals. Passive recoveries should be avoided if a person experiences vasovagal symptoms/events.